EFFECT OF APPLICATION OF RESEARCH PATTERNS FOR EDUCING CHILDREN IN PHYSICAL LESSONS - Teuku Hasan Basri; Rinto Agustino (Jurnal Pendidikan Fisika, 2018)
An effort to improve the learning outcomes of physics in the learning process in junior high school is by applying the training pattern of education, including providing motivation to students. Repeating lessons (Remedial Teaching). Measuring student learning outcomes between what is taught by educating patterns and ordinary pattern patterns. This research hypothesis the writer formulates the application of training patterns to educate physics smart children to improve physics learning achievement. The population in this study were all students in grade 1 of SMP Negeri 1 Langsa academic year 2017/2018. numbering 162 people. Samples were taken in 2 random sampling classes from the entire population, a sample of 82 people. Data collection techniques used the "Experiment" method, where class I3 was the experimental class and class I1 was the control class. The results of data processing can be concluded that by using educating patterns, students will be smart in physics lessons at SMP Negeri 1 Langsa in the academic year 2017/2018